Сучасні рішення по реконструкції газовідвідних трактів конвертерів, що працюють на металургійних підприємствах в Україні - Жидецький, Олександр Ігорович; Єфімов, Олександр Вячеславович; Каверцев, Валерій Леонідович (Національний технічний університет "Харківський політехнічний інститут", 2021)
В статті описані результати модернізації газовідвідного тракту котла-утилізатора, що встановлений в схемі газоочищення конвертерних газів на металургійних підприємствах. Представлено два варіанта схем газоочищення конвертерних газів та порівнюються характеристики котла – утилізатора старої і модернізованої конструкції. Наведена описова частина мінімально можливої реконструкції енергетичного обладнання, виконано порівняння характеристик обладнання модернізованого котла-утилізатора в порівнянні з конструкцією старого котла-утилізатора.

Nowadays most of the installed gas cleaning equipment of oxygen converters of metallurgical plants performs cleaning out of emissions of solid particles with final concentrations higher than acceptable. The inconsistency of the efficiency of the BOF-gas purification with the new emission standards entails the rejection of the emission permit and as a consequences the shutdown of metallurgical plants as well as the loss of the sales markets. In order to prevent the shutdown of the main shops of the metallurgical plants with the simultaneous implementation of appropriate environmental protection measures, it is important to launch the reconstruction of all gas-cleaning units of the converter exhaust ducts. The first element of the BOF-gas cooling and purification system is the BOF-gas cooler, its equipment is in close connection with the process equipment, thus the technological mode of steel production fully depends on its operating mode. The article describes the options ofmodernization of the exhaust duct of HRSG installed in the BOF-gas cleaning system. Besides, two options of BOF-gas cleaning system presented. In addition, two options of HRSG design: the old one and modernized – were compared.
Modern solutions for the reconstruction of gas exhaust ducts of converters operating in Ukraine
Keywords: модернізація; котел-утилізатор; газощільне виконання; багаторазова примусова циркуляція; modernization; waste heat boiler; gas-tight design; multiple forced circulation